2008
DOI: 10.1016/j.brainres.2008.07.099
|View full text |Cite
|
Sign up to set email alerts
|

Eye-movements and ERPs reveal the time course of processing negation and remitting counterfactual worlds

Abstract: The ability to update our current knowledge using contextual information is a vital process during every-day language comprehension. To understand a negated statement, readers are required to cancel real-world expectations, but are not explicitly provided with an alternative model. Thus, the question of how and when a negative context influences interpretation of later events arises. We report one eye-movement study (Exp.1) and one ERP study (Exp. 2) investigating the effects of negation on discourse processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 35 publications
4
76
3
Order By: Relevance
“…showed that sentences describing implausible real-world events (e.g., ''Families would feed their cat a bowl of carrots'') incurred temporary disruptions during sentence reading, as indexed by longer early fixations in eye-tracking, despite a counterfactual context (e.g., ''If cats were vegetarians''; see Ferguson, Scheepers, & Sanford, 2010, for evidence from visual world eye-tracking). Ferguson, Sanford, and Leuthold (2008) replicated this result with negated counterfactuals (e.g., ''If cats were not carnivores. .…”
Section: Introductionmentioning
confidence: 76%
“…showed that sentences describing implausible real-world events (e.g., ''Families would feed their cat a bowl of carrots'') incurred temporary disruptions during sentence reading, as indexed by longer early fixations in eye-tracking, despite a counterfactual context (e.g., ''If cats were vegetarians''; see Ferguson, Scheepers, & Sanford, 2010, for evidence from visual world eye-tracking). Ferguson, Sanford, and Leuthold (2008) replicated this result with negated counterfactuals (e.g., ''If cats were not carnivores. .…”
Section: Introductionmentioning
confidence: 76%
“…However, as has been demonstrated by several studies of negation (e.g. Ferguson, Sanford & Leuthold, 2008;Kaup, LŸdtke & Zwaan, 2006), representing a negative situation is frequently more difficult to process and is therefore subject to a processing delay (but cf. Nieuwland & Kuperberg, in press), which may explain why affirmative antecedent continuations are the preferred choice with the stimuli used here.…”
Section: Discussionmentioning
confidence: 92%
“…Ferguson, Sanford, and Leuthold (2008) reported that early processing disruptions as indexed by increased first-pass reading times but not in later measures coincided with an increased N400. This is consistent with observations that first fixation durations are correlated with N400 amplitude and that these measures are sensitive to the same lexical and sentence variables (e.g., Dambacher & Kliegl, 2007;see Dimigen, Sommer, Hohlfeld, Jacobs, & Kliegl, 2011, for in-depth discussion).…”
Section: Introductionmentioning
confidence: 95%